2021
DOI: 10.7575/aiac.ijkss.v.9n.4p.49
|View full text |Cite
|
Sign up to set email alerts
|

Stroboscopic Visual Training for Coaching Practitioners: A Comprehensive Literature Review

Abstract: Background: The importance of vision and its impact upon an athlete’s performance has long been recognized by elite athletic communities. In recent decades, stroboscopic training methods have been developed to help train athletes from a visual, perceptual, and cognitive perspective using strobe glasses. Objective: Herein a comprehensive literature review was conducted to investigate the effectiveness of strobe glasses in training collegiate and professional athletes. Methods: This comprehensive literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Our findings add further support to the suggestions ( Carroll et al, 2021 ; Wilkins & Appelbaum, 2020 ) that stroboscopic training may be an effective tool for improving visual and visuomotor abilities in sports training. Previous behaviors and neurophysiological evidence ( Hülsdünker, Gunasekara & Mierau, 2021a , 2021b ) showed that visuomotor reaction times after stroboscopic protocols in young elite badminton athletes were largely associated with visual processing rather than motor processes.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our findings add further support to the suggestions ( Carroll et al, 2021 ; Wilkins & Appelbaum, 2020 ) that stroboscopic training may be an effective tool for improving visual and visuomotor abilities in sports training. Previous behaviors and neurophysiological evidence ( Hülsdünker, Gunasekara & Mierau, 2021a , 2021b ) showed that visuomotor reaction times after stroboscopic protocols in young elite badminton athletes were largely associated with visual processing rather than motor processes.…”
Section: Discussionsupporting
confidence: 88%
“…One of the studies in this area was conducted by Kroll et al (2020) , who demonstrated the effectiveness of stroboscopic training in enhancing jumping performance and its potential as an addition to plyometric training in volleyball. Given that the utilization of stroboscopic protocols in a sport-specific context is a significant advantage ( Carroll et al, 2021 ), research in this field is necessary for a practical application in sport training.…”
Section: Introductionmentioning
confidence: 99%
“…Additional beneficial impacts were noted during sport-specific testing in ice hockey ( Mitroff et al, 2013 ) and badminton ( Hülsdünker et al, 2021a ). It has been suggested that these benefits are linked to more efficient processing of visual information ( Carroll et al, 2021 ; Wilkins and Appelbaum, 2020 ), which was further supported by recent neurophysiological findings of decreased activation latency in the visual motion-sensitive middle temporal (MT) area and improved reaction time ( Hülsdünker et al, 2021b ). Overall, these findings suggest that stroboscopic training can induce functional changes in the visual system, leading to faster sensory processing and improved performance in various contexts.…”
Section: Introductionmentioning
confidence: 76%
“…It is unclear how the authors came to this conclusion, as there was no reporting on adverse events in this paper. Wilkins and Appelbaum and Carrolla and colleagues both acknowledge the potential for “physical hazards” as a result of training in conditions of interrupted vision, but this is again an area that has not been explored in any of the SVT studies to date [ 1 , 65 ].…”
Section: Discussionmentioning
confidence: 99%